Airborne Bacterial Pollution in Clinical Environment, Sana'a - Yemen - Alkhyat, Salwa H.; Al-Zubairy, Maysoon Abdorhman; Alhamzi, Ebtesam Hassan; Al-qashm, Ameera M.; Al-mshrky, Anhar K. (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Abstract: This work aims to know the extent of air pollution and common bacterial species in delivery rooms in some hospitals in Sana'a city. Six randomly airborne samples from delivery rooms of three hospitals (Algmhory, Althwrah and Alsabeen hospitals). Out of 65 airborne bacteria were isolated from delivery rooms, 89.2% of them showed Gram positive bacterial isolates and 10.8% Gram negative bacteria. Bacteria isolates were identified as Staphylococcus aureus, Staphylococcus epidemidis, Micrococcus sp., Bacillus sp., Pseudomonas aeruginosa, Corynebacterium sp., Klebsiella sp., Lactobacillus sp. and Proteus mirabilis. The highest percentage of bacterial isolates was recorded in Alsabeen hospital as 66.2%. Staphylococcus was the most dominant organism isolated from the delivery rooms in all examined hospitals (37 isolates, 56.9%), while the lowest percentages were: Lactobacillus (two isolates, 3.1%), Klebsiella and Proteus (one isolate, 1.5%) for each.